Increased Mast Cell Activation in Mongolian Gerbils Infected by Hepatitis E Virus - Liu, Tianlong; Xiao, Peng; Li, Ruiwen; She, Ruiping; Tian, Jijing; Wang, Jingyuan; Mao, Jingjing; Yin, Jun; Shi, Ruihan (Frontiers in Microbiology, 2018)
Recently, mechanism study of hepatitis E virus (HEV) infection has attracted an increasing attention because of the growing rate of the acute hepatitis caused by the virus over the world. As an important initiate in the inflammation, mast cells (MCs) play a critical role in maintaining a healthy physiology. However, the function of the MCs in the acute hepatitis caused by HEV is still unclear. In the present study, mongolian gerbils infected by HEV were used as an animal model to evaluate the role of MCs in the HEV infection. The positive ELISA and RT-PCR results showed the gerbils was successfully infected with HEV. The number of mast cell in the liver and the small intestine in the infected animals were grow higher significantly than the control group. In addition, higher expression of the tryptase and 5-HT in the liver and the intestine detected by immunohistochemical method and western blot also indicate the activation of mast cells in the infection. These results suggest that MCs play an important role in the hepatitis E.